(untitled) (Journal of Partial Differential Equations, 1993)
By an involved approach a geometric measure theory is established for parabolic Monge-Amp&#232re operator acting on convex-monotone functions, the theory bears complete analogy with Aleksandrov’s classical ones for elliptic Monge-Amp&#232re operator acting on convex functions. The identity of solutions in weak and viscosity sense to parabolic Monge-Amp&#232re equation is proved. A general result on existence and uniqueness of weak solution to BVP for this equation is also obtained.